Thermal imaging of spin Peltier effect - Shunsuke Daimon (Nature Portfolio, 2016)
The spin Peltier effect produces a temperature difference along the direction of a spin current. Here, the authors use an active thermography technique to visualize the temperature modulation induced by a spin current injected into a magnetic insulator from an adjacent metal.